Surveillance Colonoscopy Revealing Asymptomatic Low-Grade Appendiceal Mucinous Neoplasm - Jagmeet S. Grewal; Elliot Berger; Jacob Garner; Jennifer S. Beaty (World Journal of Colorectal Surgery)
Appendiceal mucinous neoplasms are a collection of rare tumors with diverse clinical presentations and pathologic potential, which can pose diagnostic and therapeutic challenges. Generally, these neoplasms are either diagnosed by radiologic imaging or identified during surgery; however, they may be rarely diagnosed during an endoscopic procedure. In this case report, we present the rare case of a 62-year-old white male who was undergoing routine surveillance colonoscopy for a history of colonic neoplasia. During the colonoscopy, a submucosal, nonbleeding, 1-cm mass of benign appearance was observed in the appendix. Further workup suggested that the mass could be a mucocele, and hence surgical consultation was recommended. The patient denied any symptoms suggestive of a mucinous neoplasm prior to or during the evaluation. A laparoscopic appendectomy was subsequently performed, and the histopathology reports confirmed the diagnosis of a low-grade appendiceal mucinous neoplasm. The patient recovered without any complications and continued to deny any symptoms during his postoperative course and follow-up care. The identification of appendiceal mucinous neoplasms remains difficult because of their rare incidence and unpredictable nature. The wide spectrum of unique presentations and modalities for diagnosis is illustrated by discovering a low-grade mucinous neoplasm in an asymptomatic patient via colonoscopy. Number of similar cases published: Nil